El campo cultural e intelectual desde la perspectiva del MIR-Praxis (1955-1961) - Díaz, Javier (2021)
In this article we will analyze the way in which the intellectual and cultural field was regarded and addressed by the “Movimiento Izquierda Revolucionaria (Praxis)”. This will allow us to rebuild the conception of this political organization founded by Silvio Frondizi and to highlight the reasons for the changes it experienced. For this purpose, we will identify the voices that intervened in the cultural texts of the MIR-P press, the topics that were covered, and the type of questions addressed to intellectuals.